Health promotion & environmental activism: Haida Gwaii, Bc, the Northern Gateway Project, and a model of collective interest. - Madrid, Jessica (Author); Parkes, Margot (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2015)
This study inductively explores the theoretical connections between health promotion and environmental activism. A conceptual framework was developed that illustrates the theoretical connections between these concepts. Deductively, this study responds to a call for quantitative and case study research on the social dimensions of environmental activism and health. An empirical model of collective interest (CI), which has been used to investigate protest behaviours, was adapted to emphasize a health promotion focus and the case study context: the Canadian archipelago, Haida Gwaii, BC, and its communities' opposition towards a controversial petrochemical project, the Enbridge Northern Gateway Project. The adapted version of the CI model was used to statistically analyse survey data using logistic regression techniques that suggested predictors of activism in this context. Together, the conceptual framework and the amended CI model were integrated into an analytical framework to address the research questions and implications for health promotion practice and policy. --Leaf ii. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1976640